The development of airport city and aerotropolis - Qasim Mohammed Basim (Бескиди, 2018)
Airports are becoming new dynamic centers of economic activity, they have incorporated several commercial services and businesses, both inside passenger terminals and on their landside areas. In this process, they have taken on many features of metropolitan central business districts and established themselves as new regional development poles. Different concepts to address this type of developments can be found in the literature; this research will address the concepts of ”airport city”, “airport corridor”, and “Aerotropolis”.
Keywords: airports; airport city; airport metropolis; 725.39